ANALIS PERAWATAN MOORING WINCH DALAM MENUNJANG KELANCARAN OPERASI MOORING DAN UNMOORING DI MT. DEFIANCE - Muhammad Zacky; Rizal Rochmansyah; Bayu Yudho Baskoro; M.Kurniawan; I Kadek Laju (STKIP Subang, 2026)
Maritime safety is the top priority in ship operations, especially during mooring and unmooring activities at ports, which carry a high risk of accidents due to the use of mechanical equipment, mooring line tension, and crew activities on deck. Mooring winch plays an important role as the main equipment in supporting these operations, therefore proper maintenance is required to ensure optimal performance. This study analyzes the maintenance of mooring winch on board MT. Defiance and its role in supporting the safety and smoothness of mooring and unmooring operations. This research uses a qualitative method with data collection techniques including observation, interviews, and document studies. The results show that the implementation of maintenance has not been fully optimal, as indicated by the lack of routine inspection on components such as brake, drum, clutch, and hydraulic system, as well as the incomplete implementation of the Planned Maintenance System (PMS). The challenges faced include technical factors (component wear, decreased brake performance, and hydraulic system problems) and internal factors (lack of crew discipline, limited understanding of maintenance procedures, and suboptimal supervision). To address these issues, comprehensive measures have been taken: conducting routine inspections before and after mooring operations; applying maintenance checklists consistently; improving crew awareness through safety meetings, training, and evaluations; and strengthening supervision and coordination in maintenance activities. With proper and systematic maintenance, the mooring winch is expected to function optimally so that mooring and unmooring operations can run safely, smoothly, and efficiently.